Pengaruh Manajemen Keuangan di Kalangan Mahasiswa Sebuah Pendekatan SEM-PLS untuk Uang Saku, Gaya Hidup, Kontrol Diri, dan Literasi Keuangan - Syafiqah, Asti Dewi; Diana, Dina (Universitas Airlangga, 2024)
This study aimed to identify the factors influencing student financial management in the Jakarta Metropolitan Area. The study included 206 Jakarta Metropolitan Area respondents who met the following criteria: active students at Jakarta Metropolitan Area universities aged 17 to 25 years. The study employed the SEM-PLS method as the primary analysis approach. The results indicated that several factors showed positive and negative correlations on student financial management in the Jakarta Metropolitan Area. Specifically, self-control and financial literacy, which are internal factors, influenced financial management, while allowances and good lifestyle, which are external factors, had no influence. These findings suggest that individuals tend to manage their finances effectively when equipped with a thorough understanding of financial principles and strong self-control. The results of this study offer significant practical implications for the Jakarta Metropolitan Area government in designing strategies to increase financial inclusion more effectively. This study emphasizes the importance of self-control and financial literacy as the main factors affecting financial management skills among college students, and lifestyle factors and the amount of pocket money have no significant effect. Furthermore, financial institutions can use these findings to develop better financial products to meet consumers' preferences for sound financial principles. By providing a better understanding of the factors influencing financial management, this research can contribute to more responsible, sustainable, and compliant financial management within society.